1994
DOI: 10.1080/02786829408959683
|View full text |Cite
|
Sign up to set email alerts
|

Determination of Water Activity in Ammonium Sulfate and Sulfuric Acid Mixtures Using Levitated Single Particles

Abstract: Water activities of ammonium sulfate-sulfuric acid termiued relative to the known properties at RH about mixtures with ammonium to sulfate molar ratios be-0.75-0.90. The data were compared with other meatween 0 and 2 were measured by a spherical void surements and the estimates from the Zdanovskiielectrodynamic levitator at relative humidities (RH) of Stokes-Robinson (ZSR) method and SCAPE, a newly 0.18-0.90. Since the composition of the solid particles developed gas-particle equilibrium model, and generis sub… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
30
0

Year Published

1995
1995
2016
2016

Publication Types

Select...
8
1
1

Relationship

1
9

Authors

Journals

citations
Cited by 43 publications
(33 citation statements)
references
References 31 publications
3
30
0
Order By: Relevance
“…The growth of inorganic salts and mixtures of salts have also been studied in the laboratory using electric fields to trap single particles that are subjected to varying humidity conditions. [5][6][7][8] Results from these studies, in general, have agreed reasonably well with thermodynamic model predictions for inorganic aerosol growth. These research efforts provide a basic understanding of how inorganic aerosols respond when the relative humidity is changing and also serve as a basis for modeling the equilibrium chemistry of inorganic atmospheric aerosols.…”
Section: Introductionsupporting
confidence: 55%
“…The growth of inorganic salts and mixtures of salts have also been studied in the laboratory using electric fields to trap single particles that are subjected to varying humidity conditions. [5][6][7][8] Results from these studies, in general, have agreed reasonably well with thermodynamic model predictions for inorganic aerosol growth. These research efforts provide a basic understanding of how inorganic aerosols respond when the relative humidity is changing and also serve as a basis for modeling the equilibrium chemistry of inorganic atmospheric aerosols.…”
Section: Introductionsupporting
confidence: 55%
“…This range is typical of indoor residential environments in the Southeast controlled by an HVAC system. Data from Kim et al (1994 ) showed that the moisture uptake of ammonium sulfate (NH 4 SO 4 ) particles increases dramatically above approximately 60% RH. This suggested that significant changes in moisture uptake might be observed above this humidity and should be avoided.…”
Section: Rodes Et Almentioning
confidence: 99%
“…5 might therefore be attributed to the particles' SA core being liquid, with potential effects of SA also in the organic shell. As far as the liquid content is concerned, a very rough estimate of the liquid content (water and sulfuric acid) can be made by assuming phase separation and water uptake of sulphuric acid according to Kim et al (1994). Based on this, the water+H 2 SO 4 -volume concentration of the particles is above 60 % for the case of 0.36 SO 4 fraction, and below 31 % for the case of 0.09 SO 4 fraction.…”
Section: Phase State and Humidity-induced Phase Transitions Of Mixed mentioning
confidence: 99%